Pattern of Recurrence and Metastatic Disease in Post Operative Postradiotherapy Patients of Squamous Cell Carcinoma of Oral Cavity - Paliwal, Shruti; jakhar, Shankar lal; Chandra, Rama; Sharma, Neeti; Dhaka, Saroj; Gupta, Prachi; T, Anjali; Malav, Kapil; Khandelwal, Mayur; Dhaka, Shankar Singh (Asian Pacific Journal of Cancer Care, 2024)
Objective: Oral cavity is one of the common site of cancer in head and neck. They have high cure rate but locoregional failure seen in some cases at primary, nodal or metastatic site. We retrospectively analysed treatment results of oral cavity cancer in our institute and intented to define the prevalence and pattern of failure. Materials and Methods: It is a prospective cohort study. 179 cases of post operative oral cavity cancer between January 2019 to December 2021, who took radiotherapy or chemoradiotherapy treatment in our institute were studied. 79 patients had loss of follow up during and after treatment. Results of study excluded these patients. Results: Median follow up was 24 months (8-40 months). Treatment failure after radiotherapy or chemoradiotherapy at primary site and at nodal site was 22 % and 2 % respectively. In 8% cases recurrence was present at both primary and nodal site. Metastasis at extra nodal site occurred in 4% cases (3% in liver, 1% in bone). Conclusion: Operated case of oral cavity cancer when treated with radiotherapy or chemoradiotherapy has very high cure rate and few locoregional failures at primary and nodal site and rarely at distant site. Recurrence most commonly seen in advanced disease. Therefore, advanced disease patients should be treated with more aggressive treatment to achieve higher cure rate in oral cavity cancer patients. Disease free survival and overall survival was better in early stage than in advanced stage. Node positive disease had more risk of recurrence and metastasis.